Engineering Two‐Helix Motifs through NDI Linker: A Modular Approach for Charge Transferable Conductive Foldamers Design. Issue 1 (22nd August 2018) - Reja, Rahi M.; Misra, Rajkumar; Gopi, Hosahudya N.
Abstract: A new approach for the construction of two‐helix motifs from helix modules and planar 1, 4, 5, 8‐naphthalenetetracarboxylic diimide (NDI) is described. The single crystal conformations of two different types of two‐helix motifs consisting of achiral α‐peptide C10 ‐helix (310 ) and chiral α, γ‐hybrid peptide C12 ‐helix revealed that the helices adopted antiparallel orientations across the planar NDI with 2‐fold symmetry. The crystal conformations of two‐helix motifs were further explored to design electrical conducting peptide foldamer by introducing electron rich pyrene (p‐type) as a side‐chain in the α, γ‐hybrid helix. The two‐helix motif with charge transferable pyrene (p‐type)‐NDI (n‐type) combination showed better electrical conductivity compared to the two‐helix motif without pyrene side‐chain. Moreover, the crystal conformations also provided molecular insight into the peptide orientation of NDI‐peptide conjugates. The two‐helix motifs described here may serve as potential molecular scaffolds to design novel conductive peptide foldamers and self‐assembling biomaterials. Abstract : A new approach for the construction of two‐helix motifs using helix modules and 1, 4, 5, 8‐naphthalenetetracarboxylic diimide (NDI) is described. Single crystal analysis reveals that the two helices adopted anti‐parallel orientation across the planar NDI. Furthermore, the charge transferable (CT) two‐helix motif consisting of pyrene and NDI showed better conductivity compared to without pyrene.